Differential contribution of protein phosphatase 1α to cell transformation of different cell types - Chen, Jo‑Mei; Chen, Kun‑Chieh; Chiu, Shao‑Chih; Chen, Ru‑Yi; Hsia, Jiun‑Yi; Huang, Yun‑Ru; Yu, Chang‑Tze (Oncology reports, 2019)
Protein phosphorylation plays roles in cell transformation. Numerous protein kinase enzymes actively participate in the formation of various types of cancer by phosphorylating downstream substrates. Aurora‑A is a widely known Serine/Threonine (Ser/Thr) oncogenic kinase, which is upregulated in more than twenty types of human cancer. This enzyme phosphorylates a wide range of substrates. For example, Aurora‑A induces cell transformation by phosphorylating hepatoma upregulated protein (HURP) at four serine residues, which in turn decreases the phosphorylated levels of cell‑growth suppressive Jun N‑terminal kinase (p‑JNK). Various protein phosphatase enzymes are considered tumor suppressors by the dephosphorylation and consequent inactivation of their oncogenic substrates. Protein phosphatase 1α (PP1α), for instance, acts on Aurora‑A by dephosphorylating its substrates. However, the role of PP1α in cancer progression remains ambiguous. PP1α is overexpressed in several cancer tissues, and induces cell apoptosis and differentiation or it inhibits tumor formation in other types of cells. In addition, positive and negative correlations between PP1α expression and lung cancer development have been documented. These observations suggest the differential regulation of PP1α in various cancer tissues, or propose an ambiguous contribution of PP1α to lung cancer development. In order to investigate these contradictory conclusions, it was reported that the chromosomal region covering the PP1α locus was subjected to DNA alterations, such as gain or loss in various human cancer types by a study based on literature search. Upregulation of PP1α was noted in a collection of lung cancer tissues, and was required for the cell transformation of the lung cancer cell line A549. In contrast to this finding, overexpression of ectopic PP1α inhibited cell proliferation in 293T cells. Mechanistic studies revealed that PP1α activated AKT in A549 cells, whereas it further inactivated AKT and disrupted the HURP/JNK signaling cascade in 293T cells. Collectively, the data indicated that PP1α exerted an oncogenic function in lung cancer, while exhibiting various effects on cell transformation in different types of cells via distinct or opposite mechanisms.